2021
DOI: 10.1101/2021.09.25.461822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silicoexperiments uncover a novel mechanism underlying mutation rate evolution in sexually reproducing populations

Abstract: Natural selection is believed to universally work to lower mutation rates (MR) due to the negative impact of mutations on individual fitness. Mutator alleles have only been found to be co-selected by genetic linkage with adaptive alleles in prokaryotes. Sexual reproduction substantially reduces genetic linkage, allowing selection to effectively eradicate mutator alleles. The current understanding, therefore, is that in sexually reproducing populations selection always works to lower MR, limited by the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Because of the negative impact of most mutations on individual adaptability, natural selection is considered to be generally effective in reducing mutation rates (MR). Limited by population size, sexual reproduction will always lead to a decrease in MR, thus maintaining the stability of the genome [85][86][87]. By comparing the genomes of parents and the offspring, it was found that some species have very stable genomes [1,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the negative impact of most mutations on individual adaptability, natural selection is considered to be generally effective in reducing mutation rates (MR). Limited by population size, sexual reproduction will always lead to a decrease in MR, thus maintaining the stability of the genome [85][86][87]. By comparing the genomes of parents and the offspring, it was found that some species have very stable genomes [1,88,89].…”
Section: Discussionmentioning
confidence: 99%